The Role of the Tomohon City Government in Realizing Rice Food Sovereignty: A Study of the Regional Food Service - Tolosang, Marcelino G.P.; Ginting, Arwanto Harimas; Tarigan, Meliasta Hapri (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
Food is everything that comes from biological sources and water, whether processed or unprocessed for human consumption in the form of food and drink. Food availability is very important. Especially the availability of rice as the community's staple food. The Tomohon City Government has a role in maintaining the availability of rice as a staple food for the community through the Regional Food Service. This research uses qualitative research methods with a descriptive approach. The results of this research reveal the role of the government as a regulator in forming regulations which become a permanent legal basis for maintaining the availability of rice, the role of the dynamist is to encourage community participation to actively participate in maintaining the availability of rice through several programs such as cheap food programs, food villages and increasing the capacity of farmers and the role of facilitator. The government facilitates the farming community, such as providing modern facilities and infrastructure such as tractors and rice shedding machines and fertilizer to farmers, apart from that, the role of agricultural extension workers is to provide direct intervention to farmers to improve the quality and production of rice. Food; Rice Availability; Government Role. and fertilizer to farmers, apart from that, the role of agricultural extension workers is to provide direct intervention to farmers to improve the quality and production of rice.